Physical examination before diagnostic ultrasonography: Alive and kicking or a relic of the past? - Pavel, Andreea M.; Arita, Yuki; Kasalak, Ömer; Kwee, Thomas C. (European journal of radiology, 2025)
•Physical examination was omitted in over half of US referrals (55.6%).•Omission linked to lower reasoning and yield, but not significant after adjustment.•Skipping physical exam before US showed no clear effect on diagnostic outcomes. To investigate how often physicians perform physical examination prior to referring patients for diagnostic ultrasonography (US), and whether its omission affects clinical reasoning quality or diagnostic yield. In this prospective study, patients undergoing diagnostic US at a tertiary care center (December 2024-April 2025) were asked whether their referring physician had performed a physical examination. Patient demographics, referring specialty, healthcare professional, US indication, and anatomical region were recorded. Clinical reasoning quality (0–100%) was defined as the alignment between clinically suspected and US findings. US outcomes were classified as positive, negative, or indeterminate. Associations with omission of physical examination were analyzed using multivariate regression. Of 321 eligible patients, 302 were included (median age: 56 years; 48 % male). Physical examination was omitted in 168 cases (55.6 %). Omission was less likely in referrals from surgical specialties (odds ratio (OR) of 0.490, P = 0.032), family medicine (OR of 0.253, P = 0.016), and residents (OR 0.303, P < 0.001), as well as in cases of new complaints (OR of 0.226, P < 0.001) and head and neck US (OR of 0.261, P < 0.001). Omission was marginally associated with lower clinical reasoning scores on univariate analysis (P = 0.050), but not after adjustment. Of all exams, 51 % were positive. Omission of physical examination showed a trend toward lower diagnostic yield (P = 0.059), but was not significant after adjustment. Physical examination was frequently omitted before US referral. While initially linked to reduced clinical reasoning and diagnostic yield, these associations did not remain significant after adjustment, suggesting no clear impact on diagnostic outcomes.